The Metaverse Revolution: Transforming the Future of Retail - Harpreet Singh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of the Metaverse on the retail industry, examining how this immersive digital realm is revolutionizing traditional commerce paradigms. It investigates the convergence of cutting-edge technologies with innovative retail strategies, highlighting the evolution from static retail spaces to dynamic, AI-driven environments. It delves into real-time customer intelligence systems, adaptive retail environments, and sophisticated technical infrastructure components, including edge computing, blockchain, and artificial intelligence. The article examines practical applications such as virtual showrooms, AI-powered shopping assistants, hyper-personalized marketing, and supply chain optimization. Through extensive analysis of current industry research and market trends, this article demonstrates how the Metaverse is fundamentally reshaping customer interactions, operational efficiency, and business models in the retail sector. It reveals the critical role of emerging technologies in creating seamless, personalized shopping experiences that bridge physical and digital retail environments, while also addressing the challenges and opportunities presented by this digital transformation.